Da posse ao "mensalão": aspectos linguísticos do discurso político de Luiz Inácio Lula da Silva na Presidência da República - Carlucci Medeiros de Souza Lima (2009)
This paper directs its attention to the relations between discourse and ideology, approached based on the linguistic theory of the discourse which is focused on the articulation between intradiscourse and interdiscourse, as we show on chapter 1: Theoretical MethodologicalBasis. We analyze the political discourse of Luiz Inácio Lula da Silva fromwhen he took the position as the President of the Republic in 2003 to a political crisis that had its worst moment in July 2005 this crisis was named Mensalão. The texts selected to our research are the speech of the president when he took over the position in January 2003, the 11th Ministerial Meeting in August 2005, and the interview in the 1000th Roda Viva program of TV Cultura in November 2005. Due to the themeof this research, the discursive political field is extracted from this discursive universe, on the interdiscursive plan. In an intradiscursive format we relate the semantic pathway of the political relations (PSRP), the semantic economical pathway (PSE), the semantic pathwayof life conditions (PSCV) and the semantic pathway of the religious relations (PSRR) In chapter 2, entitled Aspects of the inauguration speech our aim is to analyze interdiscursive and intradiscursive aspects of that speech. In this chapter we identify the main themes and the main intradiscursive paths semantic in which these themes can be situated.In the level of the interdiscourse, we emphasize the oppositions between the President Lulas discourse and other discouses. In chapter 3, Aspects of the 11th Ministerial meeting, we approach the political crisistriggered in the first mandate of Luiz Inácio Lula da Silva, known as the crisis of Mensalão. On the field of the intradiscourse, we continue the identification of semantic paths (PSCV, PSE, PSRP) and its themes. Besides, in the interdiscourse, we correlate the semantic pathways to the constitutive oppositions between the President Lulas discourses andother discourses (and those of others). In chapter 4, which title is Aspects of the interview in the 1000th Roda Viva program, we identify the PSCV, PSE and PSRP in the intradiscourse through themes and figuresarticulated in the text of the interview. The relation between these semantic paths is fundamental to sustain the arguments used by Lula when he defends his point of view about the political crisis. In this chapter we analyze the defense of the President when the opposition accuses him of being permissive to Mensalão. Because of that, the persuasionstrategies become evident in this chapter. In chapter 5, The role of images, we deal with the image that President builds about himself and the country under his government. Here, we mention Pêcheux to makeexplicit the image that the sender (President Lula) builds about himself, and his receivers (journalists, spectators, political colleagues and opponents, the Brazilian population, etc) and the Mensalão crisis itself.This research allowed us to establish the image that Luiz Inácio Lula da Silva conveys about himself as a president, and about Brazil: an honest president, loyal to democratic and ethical principles, aware of the wills of millions of Brazilians. In spite of being betrayed by his colleagues who, inserted in a failed political system, involved his government in a political crisis. As to Brazil, he presets the image of a country that in spite of Mensalão, has improved its political, economical and social fields.